Bruchpilot and Synaptotagmin collaborate to drive rapid glutamate release and active zone differentiation - Paul, Mila M.; Pauli, Martin; Ehmann, Nadine; Hallermann, Stefan; Sauer, Markus; Kittel, Robert J.; Heckmann, Manfred (Frontiers in Cellular Neuroscience, 2015)
The active zone (AZ) protein Bruchpilot (Brp) is essential for rapid glutamate release at Drosophila melanogaster neuromuscular junctions (NMJs). Quantal time course and measurements of action potential-waveform suggest that presynaptic fusion mechanisms are altered in brp null mutants (brp69). This could account for their increased evoked excitatory postsynaptic current (EPSC) delay and rise time (by about one millisecond). To test the mechanism of release protraction at brp69 AZs, we performed knock-down of Synaptotagmin-1 (Syt) via RNAi (sytKD) in wildtype (wt), brp69 and rab3 null mutants (rab3rup), where Brp is concentrated at a small number of AZs. At wt and rab3rup synapses, sytKD lowered EPSC amplitude while increasing rise time and delay, consistent with the role of Syt as a release sensor. In contrast, sytKD did not alter EPSC amplitude at brp69 synapses, but shortened delay and rise time. In fact, following sytKD, these kinetic properties were strikingly similar in wt and brp69, which supports the notion that Syt protracts release at brp69 synapses. To gain insight into this surprising role of Syt at brp69 AZs, we analyzed the structural and functional differentiation of synaptic boutons at the NMJ. At ’tonic’ type Ib motor neurons, distal boutons contain more AZs, more Brp proteins per AZ and show elevated and accelerated glutamate release compared to proximal boutons. The functional differentiation between proximal and distal boutons is Brp-dependent and reduced after sytKD. Notably, sytKD boutons are smaller, contain fewer Brp positive AZs and these are of similar number in proximal and distal boutons. In addition, super-resolution imaging via dSTORM revealed that sytKD increases the number and alters the spatial distribution of Brp molecules at AZs, while the gradient of Brp proteins per AZ is diminished. In summary, these data demonstrate that normal structural and functional differentiation of Drosophila AZs requires concerted action of Brp and Sy